A peapod-like ZnO@C design with internal void space to relieve its large-volume-change as lithium-ion battery anode. Issue 2 (1st February 2018) - Hao, Yu; Wang, Shengbin; Zeng, Junsong; Li, Honglei; Yang, Puheng; Liu, Baohai; Zhang, Shichao; Xing, Yalan
Abstract: Peapod-like ZnO@C with internal void space has been synthesized by calcination of ZnO/ZnOHF@polydopamine nanorods. By designing both the large void space between particles and external elastic carbon shell, the large volume change of ZnO during charge-discharge process could be effectively relieved. Moreover, the carbon shell functioned as an electronic conductor and elastic barrier, could accelerate the reaction kinetics and confine stable SEI films formation on the outer protective layer to further improve the structural integrity. Benefiting from these structure advantages, the peapod-like ZnO@C presents a prominent electrochemical performance with a retained discharge capacity of 565.1 mA h g −1 at 0.2 A g −1 and high rate capacity of 246.6 mA h g −1 even at 4 A g −1 .